1990
DOI: 10.1007/bf01974692
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxic effect of sodium dichromate on metabolism

Abstract: The effect of sodium dichromate on cellular metabolism was investigated. Intraperitoneal injection of sodium dichromate into the rat (20 or 40 mg/kg) caused significant increases in serum lactate, pyruvate, and creatinine concentrations within 15 min after intoxication. Severe hyperglycemia occurred thereafter, as a result of increased hepatic glycogenolysis, which was seen in the first 2 h after dichromate. However, liver glycogen was resynthesized in 24 h-fasted rats after glucose refeeding. Dichromate decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…One might speculate that mitochondrial injury follows and results finally renal failure, because Cr(VI) irreversibly inhibits mitochondrial respiration in vitro (for review, see Rossi and Wetterhahn 1989). However, the toxic effects on cellular metabolism after Cr(VI) treatment of rats did not persist indefinitely, unlike the well-known metabolic inhibitors such as arsenic, cyanide, and mercury (Kim and Na 1990). In addition, metabolic disturbance has occurred with a lower dose (Kim and Na 1991 a) than the subthreshold doses of dichromate, which have been shown to have minimal effects on renal function (Christenson et al 1989).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One might speculate that mitochondrial injury follows and results finally renal failure, because Cr(VI) irreversibly inhibits mitochondrial respiration in vitro (for review, see Rossi and Wetterhahn 1989). However, the toxic effects on cellular metabolism after Cr(VI) treatment of rats did not persist indefinitely, unlike the well-known metabolic inhibitors such as arsenic, cyanide, and mercury (Kim and Na 1990). In addition, metabolic disturbance has occurred with a lower dose (Kim and Na 1991 a) than the subthreshold doses of dichromate, which have been shown to have minimal effects on renal function (Christenson et al 1989).…”
Section: Discussionmentioning
confidence: 97%
“…metabolic disturbance, occurring only in the first 2 h after dichromate treatment Na 1990, 1991 a). Ascorbate pretreatment significantly decreased dichromate-induced metabolic disturbance, the indices of which were the early hyperglycemia and BUN elevation, accompanied by depletion of hepatic glycogen and decrease in serum total amino acids, respectively (Kim and Na 1990). Pretreatment with GSH, not taken up by liver cells, decreased dichromate-induced hyperglycemia; however, it had no effect on the BUN elevation induced by dichromate 2 h after treatment.…”
Section: Statisticsmentioning
confidence: 98%
“…Cr(VI) is readily taken up by cells (Berndt 1976;Wiegand et al 1985) and causes rapid metabolic disturbance (Kim and Na 1990); however, its nephrotoxic effects are not fully expressed at the initial time periods after treatment (Biber et al 1968;Hirsch 1973;Evan and Dail 1974). As shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Rats were exposed via a single injection to 0.5, 1.25 and 2.5 mg/kg body weight (BW) CdCl 2 or 5, 10 and 20 mg/kg BW Na 2 Cr 2 O 7 . Previous studies have demonstrated the use of intraperitoneal injections of CdCl 2 [ 26 34 ] and Na 2 CrO 4 [ 35 – 38 ] in these dose ranges to induce tissue injury. Exposure times of 1, 3 and 7 days were chosen to investigate the acute effects of metal exposures and were based on previous investigations for changes in oxidative stress and recovery time [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%